Metodika razvitija skorosti udara rukami v kikboksinge - Shchapov, V. M. (Vestnik sportivnoj nauki; Sports science bulletin, 2021)
The article describes the problems of developing the speed of hand blows in kickboxing under the condition of maintaining power indicators and increasing the endurance of kickboxers. The proposed methodology of contrasting specialized exercises fulfillment, which allows to achieve the effect of increasing speed while maintaining power characteristics, fits into the basic training program of kickboxers.